THE EFFECT OF DIGITAL FINANCIAL LITERACY ON INVESTMENT DECISIONS: THE MODERATING ROLE OF FINANCIAL ANXIETY - Abdul Syukur; Fery Riyanto (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2025)
This study aims to examine the effect of Digital Financial Literacy on Investment Decision and investigate the moderating role of Financial Anxiety among stock and cryptocurrency investors in Semarang City. A quantitative approach was employed using a survey method involving 234 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Digital Financial Literacy has a positive and significant effect on Investment Decision (β = 0.405; p = 0.000). Furthermore, Financial Anxiety negatively moderates this relationship (β = -0.089; p = 0.018), suggesting that higher levels of financial anxiety reduce the effectiveness of digital financial literacy in supporting investment decisions. These findings highlight that investment decisions in the digital era are influenced by both cognitive and psychological factors. Therefore, efforts to improve digital financial literacy should be accompanied by initiatives to strengthen investors’ psychological readiness in dealing with market risks and uncertainties.